Proposta de arquitetura e desenvolvimento de API do sistema Bot Educacional utilizando os princípios de Domain-Driven Design e Arquitetura Limpa - Boussiengui, Pedro Henrique Wilfride de Lima (2023)
Recently, the use of chatbots, commonly known as bots, for text-based interactions and specific command executions has become increasingly prevalent. In this context, the Educational Bot’s emerges as an innovative system designed to function as a bot platform, providing support for both students and teachers in introductory Programming Logic cour- ses. The proposed architecture aims to modularize system components, striving for effi- cient decoupling that enhances flexibility and scalability. Throughout the development of the Educational Bot’s, robust software engineering practices were employed, incor- porating principles from Domain-Driven Design and Clean Architecture. This approach resulted in an expressive and well-defined domain, transparently reflecting the system’s business rules and use cases. The introduction of Design Patterns, such as the Reposi- tory pattern, significantly contributed to a more adaptable and extensible code structure, encouraging component reuse and simplifying continuous system maintenance. Further- more, the ap- plication of Test-Driven Development ensured the robustness and reliability of the code, establishing a solid foundation for the Educational Bot’s future evolution. This project stands as a notable example of the successful application of modern enginee- ring practices, yielding a cohesive and adaptable API. The Educational Bot’s future vision is to become a widely utilized tool across various classrooms and by numerous educators, solidifying its role as an effective solution, especially in the early undergraduate courses.